PROTECTION OF VICTIMS OF SEXUAL VIOLENCE REVIEWED FROM THE PERSPECTIVE OF LAW NUMBER 12 OF 2022 AND ISLAMIC LAW - Anita, Hoky; Ghifari, Al Khitami; Dewi, Rahayu; Monica, Mila; Rifka, Dewi; Aditia, Noor (Academic Solution Publisher, 2024)
Protection of victims of sexual violence is reviewed from the perspective of Law Number 12 of 2022 and Islamic law. Islam is a religion that is centered on the Qur'an, the holy book and the direct word of Allah SWT. All forms of actions and instructions are already stated in the holy book. In community life, there must be limitations and rules in regulating behavior and actions that are not considered to interfere with the rights of others. This is indicated by the existence of laws which mean that there are regulations that regulate relations between humans, to maintain order and peace. One of the problems faced by the country is sexual violence. Sexual violence can cause physical and psychological trauma to victims, including post-traumatic stress disorder, depression, and anxiety. This study uses comparative and descriptive methods. The descriptive method can be interpreted as a description of problems that occur in the present or are ongoing, by describing the condition of the subject or object in the study based on actual facts or as they are. The comparative method examines previous research data as a comparison of the law on sexual violence according to Law Number 12 of 2022 with the law on sexual violence according to Islam.